When islands collide : Divergence predicts outcomes of secondary contact during the fusion of Sulawesi’s paleo-archipelago - Benjamin R., Karin; Jeffrey H., Frederick; Amir, Hamidy; Awal, Riyanto; Evy, Arida; Djoko T., Iskandar; Indraneil, Das; Adi, Shabrani; Evan S., H. Quahj; Todd R., Jackman; Aaron M., Bauer; Jimmy A., McGuire (PNAS, 2025)
Downloaded from https://www.pnas.org by Benjamin Karin on October 27, 2025 from IP address 136.152.214.5. Speciation often results from the accumulation of reproductive isolation associated with lineage divergence, but secondary contact between diverged lineages can reshape the trajectory of speciation and reveal its underlying processes. The Indonesian island of Sulawesi is a tectonically complex island formed by the fusion of many paleo-islands, resulting in replicated cases of secondary contact among once-isolated lineages. Unlike secondary contact on continents where hybridization often results from unpredictable range shifts, Sulawesi’s fauna presents a replicated set of geologically constrained natural experiments to test how the magnitude of evolutionary divergence predicts outcomes of secondary contact and hybridization. Using thousands of genome-wide loci from Eutropis sun skinks spanning Wallace’s Line on Sulawesi and Borneo, we reconstructed a reticulate evolutionary history shaped by overwater dispersal, isolation, island fusion, hybridization, and character displacement. We delimited five distinct species (three undescribed) and uncovered multiple ancient hybridization events following island fusion leading to distinct outcomes. These outcomes—speciation reversal, parapatry, and sympatry putatively through reproductive character displacement—were associ- ated with increasing levels of prior divergence consistent with evolutionary theory. Sympatry, specifically, was preceded by substantial introgressive hybridization and body size divergence that likely confers reproductive incompatibility. Together, these results provide empirical support for divergence-dependent tipping points along the speciation continuum. The sun skink radiation also includes a rare instance of reverse colonization of Borneo across Wallace’s Line that established a narrowly divergent species with a uniquely intermediate body size absent from Sulawesi.